Dual Transition Effects on Sectoral Productivity Transmission in European Economies - Slimani, Salim (Industrija, 2026)
The paper presents a novel analytical framework in order to follow the diffusion of sectoral productivity shocks in European economies during both digital and green transitions. We then isolate six transmission channels by using an improved structural decomposition of input-output networks, which include; direct, internal, feedback, supplier spillovers, customer spillovers, and a new dual-transition spillover. Dynamic unbalanced panel regression includes 24 sectors in 27 EU member states between 2000-2023 and shows that there is a very large heterogeneity shock propagation in transition periods.Key results: dual transition spillovers enhance traditional network effects by 42-47 percent and digital-intensive industries by increasing upstream propagation and sustainability-oriented industries by increasing downstream transmission. The contemporary two-way transition coefficient is up to 2.34 percent, that is, much higher than traditional spillovers. Multipliers determine information services and energy as key drivers of transformation and provide spillovers that are 2.8 times greater than traditional manufacturing linkages. The temporal analysis indicates accelerating spillover effects after 2020 in line with the Recovery and Resilience Facility and the increased policies of twin-transition. Such findings offer evidence to policymakers in Europe on the dynamics of cross-sectors, highlighting the need to have integrated digital-green transition strategies in order to drive the growth in productivity.
Keywords: Network linkages, Input-output analysis, Productivity shocks, Digital transformation, Green transition, Structural decomposition, Dynamic panel regression, Twin transition, European Union